Kinetic Study on Catalytic Wet Air Oxidation of Phenol in a Trickle Bed Reactor - T. Mohammed, Wadood; M. Abdullah, Sama (Iraqi Journal of Chemical and Petroleum Engineering, 2008)
Kinetics study on the phenol oxidation by catalytic wet air oxidation (CWAO) using CuO.NiO/Al2O3 as heterogeneous catalyst is presented. 4 g/l phenol solution of pH 7.3 was oxidized in a trickle bed reactor with gas flow rate of 80% stochiometric excess (S.E).. In order to verify the proposed kinetics, a series of CWAO experimental tests were done at two temperatures (140 and 160° C), oxygen partial pressures (9 and 12 bar), and weight hourly space velocity (WHSV) (1, 1.5, 2, 2.5, and 3 h-1). According to Power Law, the reaction orders are found to be approximately 1 and 0.5 with respect to phenol concentration and oxygen solubility, respectively. These values favorably compare with those cited in the literature for intrinsic kinetics, which indicates minimal mass transfer limitations in the trickle bed reacting system used in this study.